Pengaruh Motivasi Kerja dan Disiplin Kerja terhadap Kinerja Karyawan Extrusion Blow PT. Jayatama Selaras - Harfiani Putri Aini; Zahra (PT. PENERBIT TIGA MUTIARA, 2024)
The purpose of this quantitative research is to analyze the extent to which motivation and discipline influence the performance of PT. Jayatama Selaras Extrusion Blow employees. The data collection method applies a questionnaire distributed to respondents. Researchers in this research use quantitative analysis such as validity and reliability tests, classical assumption tests, multiple linear regression analysis, hypothesis testing, and determination coefficient tests. All of these analyses were conducted using SPSS version 25. This study involved all PT. Jayatama Selaras Extrusion Blow employees, totaling 50 respondents. The saturated sample method was used to determine the sample. The results showed that with a regression coefficient of 2.145 ≥ 1.677, motivation partially has a significant effect on employee performance. With a regression coefficient of 12.914 ≥ 1.677 discipline partially has a significant effect on employee performance. It is shown that simultaneously motivation and discipline have a significant effect on employee performance, F count 256.961 ≥ F table 3.195, and the significance value of each variable ≤ 0.05. The coefficient of determination test proves that motivation and discipline influence employee performance by 95.7%, while 4.3% are factors that are not involved in this research.